EFFORT TO ESCAPE FROM THE TRADITION IN SAUDI ARABIA IN CARMEN BIN LADEN'S INSIDE THE KINGDOM: MY LIFE IN SAUDI ARABIA (2004) NOVEL: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - HANDAYANI , AGUSTINA RIZKI (2011)
The major problem of this study is to reveal how is the effort to escape from the tradition in Saudi Arabia reflected in Carmen Bin Laden's Inside the Kingdom: My Life in Saudi Arabia. The objective of this study is to analyze the novel based on its structural elements and an individual psychological approach. In analysis, the writer uses qualitative method. The object of the study is the book of Carmen Bin Laden the title is Inside the Kingdom: My Life in Saudi Arabia. The data sources consist of primary and secondary data sources. The primary data source is Inside the Kingdom: My Life in Saudi Arabia novel itself and the secondary data sources are the other sources related to the primary data such as the information about the author's biography, and websites. The method of the data collection are reading the novel, determining the character that will be analyzed, taking notes the important data, classifying and determining the relevant data, and the last is looking for the supporting data. The technique of data analysis is descriptive analysis. The outcome of the study is shown in the following conclusion. First is from the structural analysis of the novel shows that Carmen Bin Laden has some efforts to escape from many rules and traditions in her husband family and in Saudi Arabia. The second is Carmen Bin Laden has some efforts to reach her freedom. She must save her daughter from her husband family, and leaving Saudi Arabia. Her effort is done to gain her goal, free to do anything and reach the happiness in her life with her daughters.